2019
DOI: 10.1177/2167702619842468
|View full text |Cite
|
Sign up to set email alerts
|

Changing Current Appraisals of Mothers Leads to Changes in Childhood Memories of Love Toward Mothers

Abstract: False memories in therapy have previously been identified as problematic, but memory-of-emotion distortions have been underdiscussed in this context. Past research has suggested that cognitive reappraisals are associated with changes in memory of emotions. We investigated whether these findings would generalize to an important emotion (love), target (mothers), and time (childhood). In samples of adults, we manipulated current appraisals of mothers to examine the effect on memory of love felt in childhood towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
1
4
0
1
Order By: Relevance
“…Likewise, when assessing memory for motivations, Galotti (1995) found that students' recollections of the criteria they had used to select their college were biased by their current beliefs about the criteria they ought to have used. This has been confirmed in experimental research by Patihis et al (2019), who manipulated current appraisals of mothers and found significant effects on memory of love felt in childhood towards mothers. Further evidence for the distinct processes involved in recalling emotions comes from individuals with HSAM, discussed above.…”
Section: Introductionsupporting
confidence: 60%
“…Likewise, when assessing memory for motivations, Galotti (1995) found that students' recollections of the criteria they had used to select their college were biased by their current beliefs about the criteria they ought to have used. This has been confirmed in experimental research by Patihis et al (2019), who manipulated current appraisals of mothers and found significant effects on memory of love felt in childhood towards mothers. Further evidence for the distinct processes involved in recalling emotions comes from individuals with HSAM, discussed above.…”
Section: Introductionsupporting
confidence: 60%
“…The results regarding the affective judgments are also limited, especially given the inconsistent patterns and sizes of the effects observed. It is plausible that interventions aimed at modifying current mood/affect can shape the way we think about the past (e.g., Patihis, Cruz, & Herrera, 2019), though given the replicability problems that have plagued the notion that modest manipulations can have substantial effects, it is appropriate to be cautious when interpreting our results. Another limitation pertains to the specific stimuli used.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this does have a direct parallel to how we remember past feelings of love in everyday life and assess those memories. Indeed the very effect of current cognitions is one of our central interests that we are investigating in current research (Patihis, Cruz, & Herrera, 2018) and was one of the motivations for the development of the scale. Interesting future research could assess clinical populations, which may demonstrate lower mean scores on the memory of love subscales and therefore less negative skew compared to nonclinical samples.…”
Section: Discussionmentioning
confidence: 99%